PENGARUH LATIHAN METODE BLOCK SYSTEM UNTUK KETEPATAN SHOOTING FUTSAL - Erik Permana (Journal of Physical Education and Sport Science, 2021)
The purpose of this study was to determine: The effect of the block system method exercise to increase the accuracy of shooting club Nass Futsal Kuningan. This study uses experimental research methods. The population and sample in this study were the players of the Kuningan Nass Futsal club with a sample of 24 people. The research instrument used in this study was one group prettest and posttest. The results of the analysis and processing of pre-test data obtained the lowest points 17, the highest time 34. While the post-test data obtained the lowest point of 25, the highest time of 41. This indicates an increase in the shooting accuracy of the players of the Kuningan Nass Futsal club, and there is a difference the average treatment effect of block system method exercise for futsal shooting accuracy between pre test and post test based on independent sample t test.